Keefektivitasan Mind Mapping dalam Pengembangan Ide Menulis Esai Deskriptif Siswa Kelas VII MTS Al-Hidayah - Widiarti, Melia; Amri, Miftachul; Sodiq, Syamsul (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2024)
Writing is an essential talent that all pupils must possess, in addition to their listening and speaking abilities. Nevertheless, the actual situation in the field indicates that pupils' writing proficiency is comparatively deficient and falls below the average level. This research was conducted to enhance the writing skills of class VII pupils at MTS Al-Hidayah Donowari Malang by implementing the Mind Mapping approach. This study employs a quantitative experimental design. The participants in this study were eighth-grade students at MTS Al-Hidayah Donowari Malang. The research included observation and test procedures for data collection. The research utilizes Posttests of fundamental writing skills and Posttests of writing skills employing the Mind Mapping technique, which will be contrasted with standard techniques. The research data was analyzed utilizing descriptive statistical analysis techniques. The research results demonstrate the efficacy of the Mind Mapping approach in enhancing the descriptive essay writing skills of class VII-A students. The highest score achieved by a student was 95, which surpasses the minimum passing score (KKM) of 27 students, who obtained an average score of 78.5. Meanwhile, in the Conventional model, the maximum score achieved by class VII-B students in writing descriptive essays is 75, which is over the minimum passing score (KKM) of 6 students. The average score for these students is 56.667.